COOPERATIVE AGREEMENT BETWEEN PARTNERS: Negotiation And Domestic Conflict In Indonesian Islamic Law - Sifa Mulya Nurani; Soleh Hasan Wahid (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2021)
This study aims to describe cooperative negotiation techniques in the mediation process in order to ensure the survival of the household. The results show that BP4 can mediate disputes between husband and wife in the household that lead to divorce through cooperative negotiation techniques. In its application, BP4 to do; 1) internal communication with each of the disputing parties; 2) using cooperative negotiation techniques by upholding the values of togetherness; 3) give the best answer to the problems faced by the dispute; distort competitive negotiation techniques and compromise negotiation techniques if they are deemed ineffective.